Light interaction with nano-structured diatom frustule, from UV-A to NIR. Issue 57 (15th December 2015) - Maibohm, Christian; Nielsen, Josefine H.; Rottwitt, Karsten
ABSTRACT: Diatoms are found in nearly every aqueous environment and play a vital part of the global primary production system contributing with up to 25 % and are efficient light harvesting organisms. Unique to diatoms are the hard cell wall, called the frustule surrounding the single cell. The frustule is made from bio-synthesized silicate, perforated by wavelength sized features where the morphology of the nano-structured "greenhouse" is species dependent. Diatoms would therefore make for one of the most interesting "green" resources since it has not only potential as a biomass production system but also for nano-structured inorganic material. To understand the biological significance and to integrate diatomic frustules as active material in devices a fundamental understanding of how light interacts with the frustule is needed. In this study we focus on centric diatoms, i.e. having rotational symmetry where morphological parameters vary between the different investigated species. We report how light interacts with the frustule in the wavelength range from UV-A (320-380 nm) to NIR (900 nm). High resolution spectroscopy and CCD images are used to identify photoluminescence (PL) and variations in the transmitted light caused by the nano-structured frustule. Furthermore we show, by placing the frustule on a quartz half sphere how light transmission is a function of the angle of incidence and wavelength.